Socialización escolar : procesos, experiencias y trayectos - Unda Lara, René; Mayer, Liliana; Llanos Erazo, Daniel (Universidad Politécnica Salesiana ; CINDE : Universidad de Manizales, Colombia ; CLACSO, 2015)
In the articles that are part of this book, a set of themes, problems and debates are displayed that, at first, were present among the coordinating team of the book and that were later shared with the researchers who are members of the Working Group "Youth , Childhood: Policies, Cultures and Social Institutions "(GT) of the Latin American Council of Social Sciences (CLACSO). In this sense, the purpose of the compilation is to contribute to the updating of an area or field that, since its inception, was and is thought by the social sciences: the school and educational systems. However, in recent years, the field of school studies has diversified and specialized, finding new objects of study and expanding existing ones, while educational issues and problems are discussed and debated throughout society.